Study on the effect of silica fume with low calcium geopolymer properties for oil well cementing - Sugumaran, M. (Institution of Engineering and Technology, 2015)
Increasing concern of greenhouse gas emission had been a chief highlight in inducing global warming. Application of Ordinary Portland Cement (OPC) for oil well cementing contributes a large portion for these gases, and therefore, geopolymeric technology is proposed to help curb down CO2 emission by replacing OPC. However, enough justification has to be shown to ensure the new technology is reliable enough to replace OPC for oil well cementing. This study aims to study the effect of silica fume addition to low calcium fly ash geopolymer cement by focusing on compressive strength and other properties such as thickening time, fluid loss and acid resistance test. Low calcium fly ash pose geopolymeric properties besides having a very low utilization rate which justify fly ash as our base material. Further analysis on structure of cement was done via FTIR, EDX and FESEM studies. Five different composition of varying silica fume (SF) content (0, 5, 10, 15 and 20) was prepared and cured under wellbore condition (3000 psi and 200 F) slurry was 21minutes (static) and 36minutes (dynamic) and fluid loss rate 32 ml. Geopolymer cement has good resistance up to 10 HCl enough to withstand acidizing operations in wellbore. Compared to Class G cement (without addictive), geopolymer cement pose higher compressive strength and lower thickening time with high fluid loss rate. Thus, it's proven that geopolymer cement can be applicable as a replacement material for Class G cement from a shallow to medium depth cementing process. It helps to reduce greenhouse gas emissions, reduces landfill dumping issues and saves cost.